Promyelocytic leukemia protein interacts with the apoptosis-associated speck-like protein to limit inflammasome activation. - O'NEILL, LUKE (My University, 2014)
The apoptosis-associated speck-like protein containing a caspase-activating recruitment domain (ASC) is an essential component of several inflammasomes, multiprotein complexes that regulate caspase-1 activation and inflammation. We report here an interaction between promyelocytic leukemia protein (PML) and ASC. We observed enhanced formation of ASC dimers in PML-deficient macrophages. These macrophages also display enhanced levels of ASC in the cytosol. Furthermore, IL-1β production was markedly enhanced in these macrophages in response to both NLRP3 and AIM2 inflammasome activation and following bone marrow-derived macrophage infection with herpes simplex virus-1 (HSV-1) and Salmonella typhimurium. Collectively, our data indicate that PML limits ASC function, retaining ASC in the nucleus.
PUBLISHED
Keywords: Cancer